Implementasi Digital Leadership Dalam Pengembangan Kompetensi Digital Pada Pelayanan Publik Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Ambon - Pentury, Emeria; Rahawarin, Mohamad Arsad; Selanno, Hendry (Program Studi Administrasi Publik, 2025)
This study aims to analyze the implementation of digital leadership in developing digital competencies for public service at the Investment and One-Stop Service Office (DPMPTSP) of Ambon City. The research employed a qualitative approach, collecting data through in-depth interviews, observations, and documentation. The findings indicate that DPMPTSP employees possess basic understanding and adequate digital competencies, particularly in the use of electronic licensing systems, data management, and digital communication, although limitations exist in advanced features and system integration. The implementation of digital leadership by the Head of DPMPTSP and related officials encourages training, technology-based learning, and data utilization for decision-making, positively affecting employee motivation and adaptation to digital transformation. The impact of digital leadership is evident in the improvement of speed, transparency, and quality of licensing and investment services, supported by application integration, online complaints, and accessible information technology for the public. Challenges such as limited infrastructure, resistance to change, and human resource capacity are addressed through employee development, cross-sector collaboration, and the establishment of a sustainable digital ecosystem. In conclusion, digital leadership serves as a key factor in creating public services that are effective, efficient, and responsive to societal needs in the digital era.